2019
DOI: 10.1101/708164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-carboxysome formation is mediated by the multivalent and disordered protein CsoS2

Abstract: 21Carboxysomes are bacterial microcompartments that function as the centerpiece of the 22 bacterial CO2-concentrating mechanism, feeding high concentrations of CO2 to the enzyme 23Rubisco for fixation. The carboxysome self-assembles from thousands of individual proteins into 24 icosahedral-like particles with a dense enzyme cargo encapsulated within a proteinaceous shell. 25In the case of the α-carboxysome, there is little molecular insight into protein-protein interactions 26 which drive the assembly process.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…An emerging theme of CCM self-assembly is that Rubisco interacts with various CCM proteins via Short Linear Motifs (SLiMs) found in intrinsically disordered proteins/regions (IDP/Rs) (27)(28)(29). Since CsoSCA's N48-peptide appears to bind Rubisco (Fig.…”
Section: Structure Of Rubisco In Complex With Csosca Ntd Peptidementioning
confidence: 99%
“…An emerging theme of CCM self-assembly is that Rubisco interacts with various CCM proteins via Short Linear Motifs (SLiMs) found in intrinsically disordered proteins/regions (IDP/Rs) (27)(28)(29). Since CsoSCA's N48-peptide appears to bind Rubisco (Fig.…”
Section: Structure Of Rubisco In Complex With Csosca Ntd Peptidementioning
confidence: 99%
“…We purified S. elongatus McdB and found that it forms phase-separated droplets across a physiological pH-range. To our knowledge, this is the first experimental demonstration of LLPS behavior in a ParA-type ATPase partner protein and is an interesting finding given that carboxysome formation has recently been shown to involve LLPS (Oltrogge et al, 2019; Wang et al, 2019) . Collectively, these results have broad implications for understanding carboxysome formation, homeostasis, positioning, and function.…”
Section: Introductionmentioning
confidence: 63%
“…Our finding that S. elongatus McdB undergoes phase separation in vitro is intriguing on multiple fronts. First, two recent studies have demonstrated that α- and β-carboxysome formation involves LLPS (Oltrogge et al, 2019; Wang et al, 2019) . With β-carboxysomes, the protein CcmM aggregates RuBisCO to form a procarboxysome (Cameron et al, 2013) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations